ENVIRONMENTAL EFFECTS OF EXERCISE (ResearchJet Journal of Analysis and Inventions, 2023)
Physical exercise is understood as a different set of voluntary movement activities that meet the requirements of the laws of physical education and are performed consciously. Such movement activities as gymnastics, games, sports, tourism exercises were historically systematized, methodically collected and filled. The emergence of physical exercise is historically indicated in a number of textbooks (A.D. Novikov, B.A. Ashmarin, etc., 1966, 1979) as corresponding to the period of the primitive collective system.